Assessing intergenerational earnings persistence among German workers - Philipp Eisenhauer; Friedhelm Pfeiffer (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2008)
'The vitality and stability of our democracy - as well as the economy - eventually depend on the social permeability of our society.' (Horst Köhler, German Federal President, 29. 12. 2007, authors' own translation) This statement draws attention to the strong meritocratic beliefs concerning the equality of opportunity that dominate public debates. This is especially true of the education system. But does this general concern translate into a society in which one's economic success in the labor market is independent of the family into which one was born? And if so, to what degree? In this study, we investigate intergenerational earnings persistence among German workers. Our measure of labor market success is real monthly earnings before taxes and social security contributions. The relationship between fathers' and sons' labor market earnings is assessed using samples drawn from the German Socio-Economic Panel (SOEP) 1984-2006. We introduce a novel sampling procedure that allows us to observe father-son pairs at a fairly similar stage in their lives. From a variety of microeconometric estimates (utilizing both OLS and IV methods) we suggest that the best point estimate of intergenerational earnings elasticity among German workers is one-third. Hence, if in the period of investigation a father's permanent labor market earnings increased by 10 percent ( EURO 231 at the mean of our father sample), the son's long-run economic status grew by 3.33 percent. Evaluated at the mean of our sample of sons ( EURO 1,937), this implies a step up of EURO 63 for the son. This figure indicates a lower degree of mobility (and a higher degree of persistence) in Germany compared to preceding studies. In an international perspective, the intergenerational earnings persistence in Germany seems to be lower than that in the United States and higher than that in Sweden. To summarize: there still seems to be substantial intergenerational earnings mobility among German workers, but more persistence than previous research suggested.
Keywords: 330; Einkommenshöhe; Intergenerationsmobilität; Väter; Söhne; soziale Herkunft; Sozioökonomisches Panel; Persistenz; erwerbstätige Männer; Erwerbseinkommen; soziale Mobilität; Einkommensunterschied; Westdeutschland; Bundesrepublik Deutschland